Quality Assessment of Fresh and Frozen Clarias gariepinus and Tilapia zillii from Shiroro and Tagwai Dam Reservoirs in Niger State, Nigeria - Isah, Mohammed Chado; Oladipupo, Muideen Dawud; Gabi, Alhassan Usman; Usman, Ibrahim Baba (Journal of Science and Technology, 2014)
Proximate composition, mineral content and sensory evaluation of both fresh and frozen Clarias gariepenus and Tilapia zilli from Shiroro and Tagwaidam reservoirs in Niger state, Nigeria were analyzed for consumer acceptability. Forty (40) Clarias gariepenus and Tilapai zilli were purchased from fishermen at the landing sites of both Shiroro and Tagwai dams and kept in the laboratory freezer at -40C for six (6) weeks. Analysis for freshness, proximate chemical composition, and mineral composition were carried out on the samples. The data were subjected to analysis of variance (ANOVA). Significant difference (P<0.05) were obtained on the proximate composition between the two species, the percentage of total moisture and protein contents increased due to decrease in ash and lipid content throughout the weeks of both fishes from the two dam reservoirs ranging from 1.20 to 2.64% and 5.09 to 5.90% (Shiroro Clarias ash and lipid content), 1.80 to 2.58% and 4.08 to 6.87% (Tagwai Clarias ash and lipid content), 1.12 to 2.08%, 2.80 to 5.43% (Shiroro Tilapia ash and lipid content), 1.40 to 2.02%, 3.07 to 6.52% (Tagwai Tilapia ash and lipid content) respectively. There were significant difference (P<0.05) in the mineral content (calcium, magnesium, sodium and potassium). With respect to oganoleptic analyses, there was no significant difference among the parameters tested throughout the weeks except eye colour, where acceptance of Clarias from Tagwaidan was significantly higher than those from Shiroro. Thus eye colour can be regarded as on the site quality assessment parameterthat that is easily feasible.